Traços de mordidas em osso de dinossauro da Formação São José do Rio Preto, Bacia Bauru, Cretáceo Superior, Brasil - Reis, Ludimilla Fernanda dos Santos (2022)
By studying fossil bite traces, we can reconstruct the behaviour of extinct organisms and better understand past communities, ecology, and ecosystems. Herein we analyse bite traces on a fragmented sauropod rib from the Upper Cretaceous of the Bauru Basin, southeastern Brazil. The fossil was collected in the Ibirá municipality region, São Paulo State, in the strata of the São José do Rio Preto Formation (Santonian-? Maastrichtian). The analysed specimen displays nine tooth drag traces on its external surface, produced between six and seven biting events. The traces consist of shallow linear grooves, with tapered ends and a serrated or smooth edge morphology. They can be classified as Linichnus serratus, Linichnus bromleyi, and Knethichnus parallelum and were produced by an organism with ziphodont dentition, most probably an Abelisauridae. These are the first feeding traces evidences the interaction between theropods and Titanosauriformes in this geological context. This work adds to the knowledge of the Bauru Basin palaeoecology and palaeobiology and expands the record of Mordichnia of Gondwana